The effectiveness of a 0.25% lemongrass (Cymbopogon citratus) essential oil mouth spray and a 0.12% chlorhexidine mouthwash against supragingival plaque in wearers of fixed orthodontic appliances: Efektivitas mouth spray minyak atsiri daun serai (Cymbopogon citratus) 0,25% dan mouthwash klorheksidin 0,12% terhadap plak supragingiva pada pemakai peranti ortodonti cekat - Korniala; Dina Tri Ramadhani; Ricky Amran; Azmil Hadi (Makassar Dental Journal, 2026)
The use of fixed orthodontic appliances increases the risk of plaque accumulation due to the numerous retentive areas around the brackets and wires. 0.12% chlorhexidine mouthwash is the gold standard for plaque control, but its long-term use can cause side effects. Lemongrass essential oil (Cymbopogon citra-tus) possesses antibacterial activity, making it a potential safer alternative mouthwash. Differences in the effectiveness of 0.25% lemongrass essential oil mouth spray and 0.12% chlorhexidine mouthwash in reducing supragingival plaque scores were reported among students using fixed orthodontic appliances. A quasi-experimental study with a pre-test and post-test control group design was conducted on 30 participants (15 in each group). Plaque scores were mea-sured using the OHI-S before and after the intervention. Analysis was performed using a paired t-test and an independent samples t-test (?=0.05). The 0.25% lemongrass mouth spray reduced plaque scores from 56.64% to 25.44% (p=0.001). The 0.12% chlorhexidine mouthwash reduced the plaque score from 58.37% to 25.87% (p=0.001). A comparison between the groups showed p=0.762, indicating no significant difference between the two. It is concluded that both agents are equally effective in reducing plaque scores, and 0.25% lemongrass mouth spray may be a safer alternative to 0.12% chlorhexidine.